SIGNIFICANCE OF APPLYING ISLAMIC MENTAL-HEALTH PRACTICES ON THOSE AT RISK OF COVID-19 INFECTIONS (Journal of Pharmaceutical Negative Results, 2023)
This paper describe about the Islamic mental-health practices on those at risk of COVID-19 infections. It is understood that Islamic mental-health practices refers to the strength of the Islamic spirit within an individual to interact with the community around him. This is the nature of empathy and it is solely from the encouragement of Allah’s universal mercy. The low level of psychosocial is due to the person’s poor Islamic mental-cognitive process. The level of thinking of mental-cognitive process plays an important role in developing one’s psychosocial. The study also reveals the positive influence between Islamic mental-cognitive process and Islamic mental-health practices. In Islam one should always prioritize the needs of others above oneself. Islam does not recognize individualization and capitalization. Islam only recognizes the fact that genuine individuals are the ones who sacrifice themselves and their property to uphold the truth of Allah. Throughout the history of the prophets and righteous people, the trait that stands out within them are their philanthropic and egalitarian ways. These two traits will reveal intelligence when facing the problems of human life, especially for adolescents who are in their transitioning period.